Representation of the material process of Pande Bosi language in systemic functional linguistics - Husniah Ramadhani Pulungan; Nikmah Sari Hasibuan; Alfiansyah Halomoan Siregar; Nurul Hidayah; Cindy Azelia; Dinda Hafizah (Research and Development in Education (RaDEn), 2025)
Blacksmithing communities and their occupational language are increasingly overlooked amid industrial tool production, yet linguistic studies of blacksmith discourse remain scarce. This study aims to reveal the forms of material process patterns, constituent constructions, and cultural theme patterns in the Angkola blacksmith language (Pande Bosi) through the perspective of Systemic Functional Linguistics (SFL). The study addresses the limitations of previous research that has focused more on other professions, while the transitivity of Pande Bosi language has been minimally examined. Using a descriptive qualitative design, data were obtained from 20 informants aged 30–67 years in Sipange Village. Data collection employed structured interviews using listening, engaging, and speaking techniques, and the analysis followed Spradley’s content analysis model (domain, taxonomy, componential, and cultural themes). The results indicate that the material process in Pande Bosi is divided into happening and doing. Happening is marked by basic verbs and the morpheme Mar-, whereas doing appears in creative forms (non-conflated and conflated) and dispositive forms (tending to be passive). Constituent construction is dominated by actors and goals, while beneficiaries and ranges are absent due to brief spoken expressions and frequent omissions. Culturally, inversion prioritizes the process over the actor, reflecting a practical and straightforward communicative character. This study provides initial documentation of Pande Bosi transitivity as a linguistic and cultural representation of the local community.